Inferential Role and the Ideal of Deductive Logic - Thomas Hofweber (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
Although there is a prima facie strong case for a close connection between the meaning and inferential role of certain expressions, this connection seems seriously threatened by the semantic and logical paradoxes which rely on these inferential roles. Some philosophers have drawn radical conclusions from the paradoxes for the theory of meaning in general, and for which sentences in our language are true. I criticize these overreactions, and instead propose to distinguish two conceptions of inferential role. This distinction is closely tied to two conceptions of deductive logic, and it is the key, I argue, for understanding ﬁrst the connection between meaning and inferential role, and second what the paradoxes show more generally.